Isolation of highly active monoclonal antibodies against multiresistant gram-positive bacteria. - Friederike S Rossmann; Diana Laverde; Andrea Kropec; Felipe Romero-Saavedra; Melanie Meyer-Buehn; Johannes Huebner (PLoS ONE)
Multiresistant nosocomial pathogens often cause life-threatening infections that are sometimes untreatable with currently available antibiotics. Staphylococci and enterococci are the predominant Gram-positive species associated with hospital-acquired infections. These infections often lead to extended hospital stay and excess mortality. In this study, a panel of fully human monoclonal antibodies was isolated from a healthy individual by selection of B-cells producing antibodies with high opsonic killing against E. faecalis 12030. Variable domains (VH and VL) of these immunoglobulin genes were amplified by PCR and cloned into an eukaryotic expression vector containing the constant domains of a human IgG1 molecule and the human lambda constant domain. These constructs were transfected into CHO cells and culture supernatants were collected and tested by opsonophagocytic assay against E. faecalis and S. aureus strains (including MRSA). At concentrations of 600 pg/ml, opsonic killing was between 40% and 70% against all strains tested. Monoclonal antibodies were also evaluated in a mouse sepsis model (using S. aureus LAC and E. faecium), a mouse peritonitis model (using S. aureus Newman and LAC) and a rat endocarditis model (using E. faecalis 12030) and were shown to provide protection in all models at a concentration of 4 μg/kg per animal. Here we present a method to produce fully human IgG1 monoclonal antibodies that are opsonic in vitro and protective in vivo against several multiresistant Gram-positive bacteria. The monoclonal antibodies presented in this study are significantly more effective compared to another monoclonal antibody currently in clinical trials.